Kinerja Algoritma Yamamoto’s Recursive Code dan Algoritma Fixed Length Binary Encoding pada Kompresi File PDF - Yulrismawati Sihura; Taronisokhi Zebua; Hukendik Hutabarat (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The use of files in digital form is currently growing and requires media to store them. The more files that store, the more storage space need. This encourages the development of file reduction techniques or data compression techniques with the aim of reducing the required storage space. The compression technique has several algorithms that can be used to compress files such as Yamamoto's recursive code algorithm and Fixed Length Binary Encoding (FLBE). These algorithms have different performance to produce quality compressed results, so they need to be compared. This study describes the analysis and comparison of the performance of the two algorithms based on the exponential method as measured by the quality of the compressed pdf file. The exponential comparison method is one of the methods of the Decision Support System (DSS) to determine the priority order of decision alternatives with multiple criteria. Compression quality parameters that are measured as an alternative comparison are the value of the ratio of compression, compression ratio, space saving. Based on the results of the comparison with Exponential Comparison Method (MPE), it was found that the fixed length binary encoding algorithm has a better performance with a value of 2.55% compared to the Yamomoto's recursive code algorithm with a smaller value of 2.22%.